Spelling impairments in Spanish dyslexic adults - Afonso, Olivia; Suárez-Coalla, Paz; Cuetos, Fernando (Frontiers in Psychology, 2015)
Spelling deficits have repeatedly been observed in children with dyslexia. However, the few studies addressing this issue in dyslexic adults have reported contradictory results. We investigated whether Spanish dyslexics show spelling deficits in adulthood and which components of the writing production process might be impaired in developmental dyslexia. In order to evaluate the involvement of the lexical and the sublexical routes of spelling as well as the graphemic buffer, lexical frequency, phonology-to-orthography consistency and word length were manipulated in two writing tasks: a direct copy transcoding task and a spelling-to-dictation task. Results revealed that adults with dyslexia produced longer written latencies, inter-letter intervals, writing durations and more errors than their peers without dyslexia. Moreover, the dyslexics were more affected by lexical frequency and word length than the controls, but both groups showed a similar effect of P-O consistency. Written latencies also revealed that while the dyslexics initiated the response later in the direct copy transcoding task than in the spelling-to-dictation task, the controls showed the opposite pattern. However, the dyslexics were slower than the controls in both tasks. Results were consistent with the hypothesis that spelling difficulties are present in adults with dyslexia, at least in a language with a transparent orthography such as Spanish. These difficulties seem to be associated with a deficit affecting both lexical processing and the ability to maintain information about the serial order of the letters in a word. However, the dyslexic group did not differ from the control group in the application of the P-O conversion procedures. The spelling impairment would be in addition to the reading deficit, leading to poorer performance in direct copy transcoding compared to spelling-to-dictation.